LC/MS/MS Analysis of N-Terminal Protein Adducts with Improved Sensitivity: A Comparison of Selected Edman Isothiocyanate Reagents - Per Rydberg; Hans von Stedingk; Jörgen Magnér; Jonas Björklund (International Journal of Analytical Chemistry)
This study provides a basis for a new and straightforward method for LC/MS/MS-based screening of N-terminal protein adducts. This procedure is denoted the “FIRE procedure” as fluorescein isothiocyanate (FITC) gave superior sensitivity by LC/MS/MS when measuring adducts (R) of electrophilic compounds with a modified Edman procedure. The principles of the FIRE-procedure are that adducts to N-terminal amino acids selectively are detached and measured from of proteins after derivatisation by isothiocyanate Edman reagents. In this study, FITC, 4-N,N-dimethylaminoazobenzene 4′-isothiocyanate (DABITC) and 4-dimethylamino-1-naphthyl isothiocyanate (DNITC) were used to synthesize thiohydantoin analytes from valine and N-methylvaline. The sensitivity by LC/MS/MS was enhanced by up to three orders of magnitude as compared to phenyl isothiocyanate and higher as compared to pentafluorophenyl isothiocyanate. The FITC reagent will enable measurements of low background adduct levels. Synthesized analytes were characterised with, for example, H1 NMR, C13 NMR, LC/MS/MS, and UV.